Comparative Risks of Fracture Among Direct Oral Anticoagulants and Warfarin: A Systematic Review and Network Meta-Analysis - Tsai, Sung Huang Laurent; Hu, Ching-Wei; Shao, Shih-Chieh; Tischler, Eric H.; Obisesan, Olufunmilayo H.; Vervoort, Dominique; Chen, Wei Cheng; Hu, Jiun-Ruey; Kuo, Liang-Tseng (Frontiers in Cardiovascular Medicine, 2022)
Importance: Previous studies have shown the effectiveness and safety of direct oral anticoagulants (DOACs), including lower fracture risks, compared to warfarin. However, direct or indirect comparisons between different DOACs are scarce in the literature. Objective: This study aims to compare fracture risks among different DOACs and warfarin, including apixaban, rivaroxaban, dabigatran, and edoxaban, in patients with non-valvular atrial fibrillation (NVAF) or venous thromboembolism (VTE). Methods: We searched PubMed/MEDLINE, Embase, Cochrane CENTRAL, and Web of Science for randomized controlled trials and cohort studies comparing the fracture risks among patients who used warfarin or DOACs, up to March 2021. Two authors extracted data and appraised the risk of bias of included studies. The primary outcome was fracture risk. We performed pairwise meta-analyses to compare differences between medications and network meta-analyses using frequentist random- effects models to compare through indirect evidence. We used P-score to determine the probability of a DOAC ranking best in terms of fracture risk. Results: Thirty-one studies were included in the final analysis. Twenty-four randomized controlled trials and seven cohort studies with 455,343 patients were included in the systematic review and network meta-analysis. Compared to warfarin, the risk of any fractures was lowest with apixaban (relative risk (RR) = 0.59; 95% confidence interval (CI): 0.48-0.73), followed by rivaroxaban (RR: 0.72; 95% CI: 0.60-0.86), edoxaban (RR: 0.88; 95% CI: 0.62-1.23), and dabigatran (RR = 0.90; 95% CI: 0.75- 1.07). No substantial inconsistency between direct and indirect evidence was detected for all outcomes. Conclusions: All DOACs were safer than warfarin concerning the risk of fracture; however, apixaban had the lowest relative risk of fracture within the class of DOACs. Further head-to-head prospective studies should confirm the comparative safety profiles of DOACs regarding fractures.